Proteção social especial de assistência social na grande Cuiabá : análise da política de atendimento do CREAS à criança e ao adolescente vítimas de violência sexual - Arruda, Terezina Fátima Paes de (2012)
This study now presents itself as an object of study takes the analysis of Special Protection Social Welfare electing as cropping, the attendance policy of CREAS - Specialized Centers of Social Welfare - child and adolescent victims of sexual violence in the Great Cuiabá, in the period from 2006 to 2010. The current format of PNAS - National Policy for Social Assistance - and its development through ITS - Unified Social Assistance System - define your responsibility as a special social protection that has the institutional space CREAS operating in the municipalities. Theoretically, these spaces were the organizers of a major network of organizations, agencies and institutions, in order to address the problems experienced by users of special social protection. Its purpose constitutes the regulation and organization of care to the needs of social security and protection to children and adolescents nationwide through an interrelated continuum of services, benefits, programs and projects, aiming to ensure and strengthen the provisions of Law Organic Social Assistance LOAS/1993. The research encompassed two cities of Cuiabá, state of Mato Grosso, selected intentionally because they have already deployed care services as recommended by PNAS and hence by ITS. The procedures used to achieve the goals and analysis of the first and second section of this study are made up of bibliographic and documentary research. In the third section of this study, the instrument used was a focused interview with the technical teams that work directly on the network of Care Policy for Children and Adolescents Victims of Sexual Violence in CREAS of Cuiabá. The results indicate that children and adolescents continue to suffer the consequences of acts that could and should be avoided if the Social Protection Network actually acted in a coordinated manner.